2009
DOI: 10.1016/j.clinph.2009.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Vocalization-induced enhancement of the auditory cortex responsiveness during voice F0 feedback perturbation

Abstract: Objective The present study investigated whether self-vocalization enhances auditory neural responsiveness to voice pitch feedback perturbation and how this vocalization-induced neural modulation can be affected by the extent of the feedback deviation. Method Event related potentials (ERPs) were recorded in 15 subjects in response to +100, +200 and +500 cents pitch-shifted voice auditory feedback during active vocalization and passive listening to the playback of the self-produced vocalizations. Result The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
179
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 144 publications
(208 citation statements)
references
References 40 publications
24
179
5
Order By: Relevance
“…The subsequent vocal compensation for the change in vocal feedback resulted in a correction of the auditory cortex neural responses back toward the normal vocalization-related neural activity. This suggests that auditory cortex may play a role in vocal feedback monitoring as suggested by earlier studies (Houde et al, 2002;Eliades and Wang, 2008a;Tourville et al, 2008;Behroozmand et al, 2009). This observation is empirically important and conceptually interesting because it reflects the expected events underlying feedback-dependent vocal control.…”
Section: Auditory-vocal Interaction and The Lombard Effectsupporting
confidence: 70%
See 1 more Smart Citation
“…The subsequent vocal compensation for the change in vocal feedback resulted in a correction of the auditory cortex neural responses back toward the normal vocalization-related neural activity. This suggests that auditory cortex may play a role in vocal feedback monitoring as suggested by earlier studies (Houde et al, 2002;Eliades and Wang, 2008a;Tourville et al, 2008;Behroozmand et al, 2009). This observation is empirically important and conceptually interesting because it reflects the expected events underlying feedback-dependent vocal control.…”
Section: Auditory-vocal Interaction and The Lombard Effectsupporting
confidence: 70%
“…We previously predicted such a role of vocalization-induced suppression based upon neural activities during frequency-shifted changes in vocal feedback (Eliades and Wang, 2008a). Recent evidence from human studies confirms this increase in auditory cortex sensitivity during speech (Behroozmand et al, 2009;Greenlee et al, 2011). It has also been suggested that suppression occurs when there is a match between expected and perceived feedback, and that the increased activity during masking reflects a mismatch due to absence or reduced feedback (Houde et al, 2002).…”
Section: Masking and The Origins Of Vocalization-induced Suppressionmentioning
confidence: 88%
“…The first experiment was done on vocal responses from a previously published study involving electro-encephalography (EEG) recordings in response to brief (200 ms) pitch-shift stimuli (PSS) in the middle of vocalization. The PSS had a predictable direction (all upward), but their magnitudes were randomized at þ100, þ200, and þ500 cents (Behroozmand et al, 2009). In that study, nearly 100 trials were recorded for each PSS magnitude (þ100, þ200, þ500 cents), which allowed the examination of many more trials than what has been reported previously.…”
Section: Introductionmentioning
confidence: 99%
“…In that study, nearly 100 trials were recorded for each PSS magnitude (þ100, þ200, þ500 cents), which allowed the examination of many more trials than what has been reported previously. A shortcoming of the study of Behroozmand et al (2009) was that the anticipation of the predictable stimulus direction by the subjects may have influenced their vocal responses to the stimuli. Therefore, a second experiment was carried out that consisted of three separate blocks of trials in which the predictability of the stimulus direction was varied.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this system allows for the differentiation between self-generated and external stimulation Ford & Mathalon, 2004;Ford et al, 2007;Heinks-Maldonado et al, 2005;HeinksMaldonado et al, 2007). On the contrary, if the voice feedback and the predicted sensory consequences do not match, an error signal is generated, and hence auditory cortical suppression is reduced (i.e., auditory activity is increased; Behroozmand, Karvelis, Liu, & Larson, 2009;Eliades & Wang, 2008;Heinks-Maldonado et al, 2005;Heinks-Maldonado et al, 2007;Sitek et al, 2013). Complementing these studies, recent evidence (Tian & Poeppel, 2013 has shown that the operation of the internal feedforward system is not an Bartifact^of overt vocal production, since it operates during articulation imagery.…”
mentioning
confidence: 99%